Problems in Classifying Gender Relations Verses: An Analysis of Musdah Mulia and Faqihuddin Abdul Kodir - Ida Kurnia Shofa; Hamdani Anwar; Romlah Widayati (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study addresses ongoing debates in feminist Qur’anic interpretation in Indonesia, focusing on epistemological ambiguities in classifying verses on gender relations. It aims to critically compare the interpretive methodologies of Musdah Mulia and Faqihuddin Abdul Kodir, two influential scholars representing different feminist hermeneutical approaches. Employing qualitative library research with a critical-comparative and epistemological framework, this study analyzes their main works and relevant supporting literature. The findings show that Musdah Mulia promotes a humanist-feminist interpretation that prioritizes gender justice and equality as the Qur’an’s primary ethical horizon. Although effective in challenging patriarchal interpretations, this approach raises epistemological issues due to its reliance on external ethical standards to distinguish normative from historical verses. Conversely, Faqihuddin Abdul Kodir’s Qirā’ah Mubādalah treats all verses as normative through the reconstruction of reciprocal gender relations, offering greater structural consistency but creating tension between textual fidelity and hermeneutical reconstruction based on mutual ethics. This study concludes that both approaches reflect a fundamental structural problem in feminist Qur’anic interpretation: the absence of a coherent Qur’anic theoretical framework integrating ethics, textual authority, and methodology. It recommends the development of an integrative interpretive model grounded in internal Qur’anic epistemology to strengthen future feminist exegesis.